Stress levels, coping strategies, and mental health literacy among secondary school students in Kenya - Ayiro, Lilian; Misigo, Bernard Lushya; Dingili, Rodgers (Frontiers in Education, 2023)
Abstract Stress is a risk factor of mental health problems such as anxiety, depression, substance use, sleep problems among others. Data in sub-Saharan Africa estimate that up to 20% of children and adolescents experience mental health problems as a result of stress due to the nature of their developmental stage associated with neurobiological, hormonal, psychological, and social changes. They also experience others common stressors such as school life demands, poverty and family problems. The emergence of Covid-19 pandemic also exacerbated stress, and mental health problems across all populations in the world. This study sought to answer the following questions: What is the stress level of students in secondary schools in Kenya? Is there a significant difference in stress levels among boys and girls in secondary schools in Kenya? What is the literacy level of the boys and girls in secondary schools in Kenya on mental health issues? We employed a sequential explanatory mixed method research design. A total of 151 (39%) boys and 232 (61%) girls aged 16-22 learning in secondary schools in Kenya participated in the quantitative study. Results showed that 11(3%) of the students perceived themselves to be having low stress, 244(66%) were moderately stressed and 112(31%) perceived to themselves to be highly stressed. The study also found that girls perceived themselves to be more stressed, (M = 2.53, SD = .55) compared to boys (M = 2.24, SD = .540, t = -4.926, df = 378, p<.001. Focus group discussions on literacy level of students revealed the following emergent themes: Students attempted to define stress and mental health, students attributed stress and mental health problems to school, peer, and home pressure. Lastly, students believed that seeking social, psychological support were the best way to cope with stress and mental health problems. The findings will be useful in developing awareness programs on mental health issues in secondary schools in Kenya.